THE EFFECT OF DISCOVERY LEARNING MODELS AND COGNITIVE STYLES ON RESULTS OF IPS LEARNING AT SDN 06 KETOL, CENTRAL ACEH - Rizal Nuari; Samsidar Tanjung; Wildansyah Lubis (SENSEI RESEARCH CENTER, 2021)
This research purpose to: (1) determine the differences in student learning outcomes using the Discovery Learning model and student learning outcomes using the Direct Instruction learning model; (2) Knowing the differences in learning outcomes of students who have a Field Independent (FI) cognitive style with students who have a Field Dependent (FD) cognitive style; (3) Knowing the interaction of Discovery Learning models with learning styles in students in increasing learning outcomes. The sample in this study were the fourth grade students of SD Negeri 06 Ketol, Aceh Tengah Regency, in the academic year 2020/2021 as many as 40 students. Collecting data in this study through cognitive style tests and social studies learning outcomes tests. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) The social studies learning outcomes of students taught by discovery learning model were higher than direct instruction learning models (Fcount = 15.681 and sig. 0.000> 0.05); (2) Social studies learning outcomes of students who have a field independent cognitive style are higher than students who have a field dependent cognitive style (Fcount = 4.395 and a sig. 0.043> 0.05) and (3) There is an interaction between the learning model and the cognitive style. in influencing student social studies learning outcomes (Fcount = 7.696 and sig. 0.009> 0.05).